The development of manufacturing industry in Egypt, Israel & Turkey - United Nations (New York, 1958)
The study is primarily concerned with the growth of medium-scale and large-scale manufacturing establishments
Bibliographical footnotes.
mf24/01/2019
Loans
Keywords: Manufacturing industries; Manufacturing industries; Manufacturing industries